Teacher Autonomy and Technology-Mediated Instruction: Organizational and Social Determinants in Rivers Secondary Schools - Eboh Rhoda Nkemdilim (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
This paper analyses teacher autonomy and the extent of the use of technology in teaching and the social and organizational variables in Rivers State Secondary Schools. Using a descriptive correlational approach, data was gathered from 366 teaching staff in 12 public secondary schools. The results show a statistically significant positive correlation between teacher autonomy and the extent of use of technology in teaching (r = 0.62, p < 0.05). Of the organizational variables, social variables predict teacher autonomy, whereas social variables predict the extent of use of technology in teaching. Self-Determination Theory, Organizational Climate Theory, and TPACK help to unpack the results. The results show that more institutional support and a more collaborative school culture increases the level of digital pedagogy used. The authors call for a more decentralized approach to policy formulation, changes in the way administrators do things and more teacher training.